Lowering the thermal noise barrier in functional brain mapping with magnetic resonance imaging - Luca Vizioli (Nature Portfolio, 2021)
The signal-to-noise ratio is a key consideration when selecting a magnetic resonance imaging protocol. Thermal noise is major issue, especially in high resolution functional images. Here the authors introduce a method to suppress thermal noise in functional images without losses in spatial precision, increasing the signal-to-noise ratio.